The mathematical model of computer keyboard - Juškevičienė, Anita (Lietuvos matematikos rinkinys, 2009)
A lot of countries have their own computer keyboards which are constructed allowed for some parameters and their language peculiarity. It is interesting to find out: is the keyboard effective? The main aim of this work is to create the mathematical model of computer keyboard which will help to measure the efficiency of different computer keyboard layouts without experiment using once counted letters rates and fingers quickness.